Perspectives of environmental management in Brazilian fashion: a study of practices in the production of jeans - Wachholz, Larissa Aparecida; Rezende, Luciana Cristina Soto Herek; Grossi-Milani, Rute; Lizama, Maria de los Angeles Perez (Electronic Journal "Fórum Ambiental da Alta Paulista", 2023)
This study aims to diagnose environmental management practices adopted by industries in the jeans production chain and present new and sustainable solutions to reduce environmental damage throughout the production processes. Through bibliographic research, documentaries, and semi-structured interviews, it was possible to diagnose several actions proposed by the present company to reduce environmental damage and contribute to achieving social justice.  Thus, the research is significant, as the textile sector has excellent potential for achieving the SDGs in Brazil, especially when considering the growth of the world market of jeans, tied to various environmental and social impacts throughout the production process. Initiatives taken by other companies in the sector were identified, indicating new possibilities that can be adapted to the reality of several organizations to use them as a reference in mitigating environmental impacts. Regarding the company analyzed, it was observed that there is a stance on pollution control, considering the various initiatives that seek to mitigate social and environmental issues. However, it is suggested that the company has many mechanisms and paths to evolve toward pollution prevention postures or even a strategic approach, which will ensure a better performance in the implementation of new sustainable practices.